Pemetaan Sebaran Domisili Mahasiswa Menggunakan Leaflet Maps Pada Sistem Informasi Eksekutif - Rizal, Randi; Sumaryana, Yusuf (Jurnal ICT : Information Communication & Technology, 2020)
One of the problems at the university level is the unmapped data of students so that executives on campus have difficulty in recompiling the data on the distribution of the student's domicile. In order for the executive to get supporting data in determining decisions so that promotion of university introduction can be spread to various regions, an information system for disseminating student data based on their domicile is needed. This research has implemented a leaflet map with the Extreme Programming (XP) system development method to visualize the student domicile map in the executive information system. In the previous study, only a node or point in the visualization of the distribution of student data, the researcher used a leaflet map because it was more visualizing with a color graphic showing the amount of data distribution.